Comparative outcomes of operable non-inflammatory and non-metastatic inflammatory breast cancer in Morocco: a retrospective cohort study - Ismaili, Nabil; Guessous, Fadila; El Majjaoui, Sanaa (Frontiers in Oncology, 2025)
BackgroundOutcomes of non-metastatic non-inflammatory breast cancer (non-IBC) and inflammatory breast cancer (IBC) in Moroccan women remain poorly defined. The aim of this study was to compare patient demographics, tumor characteristics, and survival outcomes between women with operable non-IBC and those with non-metastatic IBC in Morocco.MethodsWe retrospectively analyzed data from 472 patients diagnosed with non-metastatic non-IBC (n=400) or non-metastatic IBC (n=72) and treated at the National Institute of Oncology, Rabat. Non-IBC patients were included between January 2001 and December 2003, whereas IBC patients were included between January 2007 and December 2008.ResultsThe median age of patients was 45.8 years (range, 22–91 years). The majority of patients were diagnosed at AJCC stage III or higher (61%), and 72.7% presented with lymph node involvement. Approximately 95% of patients completed multimodal therapy including surgery, chemotherapy, and radiotherapy. Mastectomy and breast-conserving surgery were performed in 82% and 12.9% of cases, respectively. Radiotherapy was delivered to 95.1% of patients. After a mean follow-up of 54.6 months (range, 1–101 months), 5-year disease-free survival (DFS) and overall survival (OS) rates were 75.3% and 80.5%, respectively. At 3-years, OS was significantly lower in the IBC cohort (59.2%) compared with the non-IBC cohort (91.4%) (p<0.0001). Moreover, OS at 3 years was significantly lower in IBC patients compared with stage III non-IBC patients (p<0.001). However, when treated with multimodal therapy, survival outcomes were similar between IBC and stage III non-IBC patients. In the overall population, prognostic analysis showed that positive lymph node status (OS and DFS: p<0.001), advanced T stage (pT4 vs. pT1–pT3, OS: p=0.078, DFS: p<0.001), and AJCC stage (stage III-IBC vs. stage III non-IBC vs. stage I–II, OS and DFS: p<0.0001) were predictive of poorer OS and DFS.ConclusionsBreast cancer in Moroccan women exhibited more aggressive behavior, with diagnosis often occurring at younger ages and more advanced stages. IBC patients had significantly worse outcomes compared with stage III non-IBC patients. Our findings underscore the importance of multimodal treatment, surgery, chemotherapy, and radiotherapy, in improving survival, particularly for stage III and IBC patients. Early-stage (I–II) disease was associated with favorable outcomes.